Penerapan Model Pembelajaran Active Learning Berbantuan Media Pembelajaran Educaplay dalam Meningkatkan Minat Belajar pada Pendidikan Agama Islam dan Budi Pekerti di Kelas VA SDN 23 Batara Palopo - Arif, Nurcholis; Madehang; Ervi Rahmadani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study was motivated by the low level of student engagement and learning interest in Islamic Religious Education at grade V of SDN 23 Batara, caused by monotonous teaching methods and limited use of interactive media. The study aimed to describe learning activities and improve students’ learning interest through the implementation of the Active Learning model assisted by Educaplay media. This research used Classroom Action Research (CAR) based on Kurt Lewin’s model, conducted in two cycles consisting of planning, action, observation, and reflection. The subjects were 13 students. Data were collected through observation, interviews, and questionnaires. Data analysis was conducted qualitatively and quantitatively using percentage calculations. The results showed that learning activities increased from 67.30% in cycle I to 96.15% in cycle II. Students’ learning interest also improved from 69.47% to 78.50%. These findings indicate that the Active Learning model assisted by Educaplay is effective in improving students’ learning activities and interest